PRODUCT DESIGN DEVELOPMENT TO INCREASE CUSTOMER ATTRACTION: (Study on Terrace Kitchens in Makassar City) - Agus Syam; Syafira Ayu Amalia; Muhammad Rakib; Sudarmi Sudarmi; Nurhidayanti S. (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
Product development is a continuous endeavor for owners to enhance the level of consumer acceptance of their products. The introduction of new or updated products is a strategy employed by owners to thrive in a competitive market, where meeting consumer needs and increasing product value are crucial for business success. This study focuses on developing business products by identifying consumer expectations for Dapur Teras products, which are then refined using the Research and Development concept. The research methodology follows the ADDIE development model, encompassing Analysis, Design, Development, Implementation, and Evaluation stages. Data was gathered through a survey involving 30 customers who had purchased Dapur Teras products, and the findings were presented using graphs and tables. The results indicate that Product Quality, Product Taste, and Product Packaging significantly influence the success of Makassar City Terrace Kitchen products. The unique taste of terrace kitchen products provides a competitive edge, influencing consumer preferences and satisfaction levels.